Uso de las tecnologías de la comunicación en las relaciones de trabajo y su impacto durante y después pandemia - Zuta Palacios, Karla (2023)
Through the hereby article, the author reviews the main standards that regulate the usage of communication information within workplace relationships; on an individual and collective level. And their use during the pandemic is possible after a sanitary emergency.